Color Point Tuning by Partial Ba2+ Substitution of Ca 2+ in (Ca1-xBax)3(PO 4)2 Phosphor for White Light Emitting Diodes - Li, Y.; Yu, H.; Deng, D.; Hua, Y.; Zhao, S.; Jia, Guohua; Wang, H.; Huang, L.; Li, Y.; Li, C.; Xu, S. (Elsevier, 2013)
A potential phosphor (Ca1-xBax)3(PO 4)2:Eu2+ was synthesized by a solid-state reaction. X-ray diffraction (XRD) analysis confirmed the formation of (Ca 1-xBax)3(PO4)2 crystal phase. With the Ba2+ content increasing, the bandgap of (Ca 1-xBax)3(PO4)2 increases from 5.5 to 5.9 eV, and the crystal field splitting between the two lowest Eu2+ 5d levels is enhanced from 6085 to 6808 cm-1 in (Ca1-xBax)3(PO4)2. As a result, the emission peak of (Ca1-xBax) 3(PO4)2: Eu2+ shifts from 447 to 550 nm, which means that the emission color alters from blue to yellow. The redshift of the emission band of (Ca1-xBax) 3(PO4)2:Eu2+ was explained based on crystal field strength, covalence, Stokes shift. The results revealed that partial substitution of Ca2+ by Ba2+ ions was therefore a much considerable way to shift the color point of LEDs. © 2013 Elsevier Inc. All rights reserved.